Role of Interleukin-10 in Acute Brain Injuries - Garcia, Joshua M.; Stillings, Stephanie A.; Leclerc, Jenna L.; Phillips, Harrison; Edwards, Nancy J.; Robicsek, Steven A.; Hoh, Brian L.; Blackburn, Spiros; Doré, Sylvain (Frontiers in neurology, 2017)
Interleukin-10 (IL-10) is an important anti-inflammatory cytokine expressed in response to brain injury, where it facilitates the resolution of inflammatory cascades, which if prolonged causes secondary brain damage. Here, we comprehensively review the current knowledge regarding the role of IL-10 in modulating outcomes following acute brain injury, including traumatic brain injury (TBI) and the various stroke subtypes. The vascular endothelium is closely tied to the pathophysiology of these neurological disorders and research has demonstrated clear vascular endothelial protective properties for IL-10. and models of ischemic stroke have convincingly directly and indirectly shown IL-10-mediated neuroprotection; although clinically, the role of IL-10 in predicting risk and outcomes is less clear. Comparatively, conclusive studies investigating the contribution of IL-10 in subarachnoid hemorrhage are lacking. Weak indirect evidence supporting the protective role of IL-10 in preclinical models of intracerebral hemorrhage exists; however, in the limited number of clinical studies, higher IL-10 levels seen post-ictus have been associated with worse outcomes. Similarly, preclinical TBI models have suggested a neuroprotective role for IL-10; although, controversy exists among the several clinical studies. In summary, while IL-10 is consistently elevated following acute brain injury, the effect of IL-10 appears to be pathology dependent, and preclinical and clinical studies often paradoxically yield opposite results. The pronounced and potent effects of IL-10 in the resolution of inflammation and inconsistency in the literature regarding the contribution of IL-10 in the setting of acute brain injury warrant further rigorously controlled and targeted investigation.